THE STRATEGY OF STRUCTURING INFORMATION ACCORDING TO ITS RELEVANCE IN MIND MANIPULATION - Dmytruk, Olga (Advanced Education, 2018)
The article deals with the linguistic means of mind manipulation and the strategy of structuring information according to its relevance. The author offers an overall classification of manipulation strategies and tactics and goes on to analyse how the strategy of structuring information according to its relevance is implemented in various communicative situations. The article focuses on giving a detailed analysis of the strategy and linguistic and extra-linguistic means used to manipulate the addressee. The author looks into the theoretical grounds of “the compliment sandwich” along with its practical application in communication, analysing a failed attempt of this act and offering an explanation why the act was unsuccessful. The author also demonstrates how an act of mind manipulation may be successful even after the addressee realises they have been manipulated, offering reasons for such an outcome. Special attention is given to the analysis of mind manipulation act where the target is guided by the manipulator from beginning to end, without realising of being manipulated. The article maintains that a successful manipulation act is based on a variety of techniques as well as the knowledge of the addressee’s personal traits and the dexterity of the manipulator. Verbal means are enforced by non-verbal ones producing the desired effect.